1995
DOI: 10.1128/mcb.15.3.1522
|View full text |Cite
|
Sign up to set email alerts
|

The PAX3-FKHR Fusion Protein Created by the t(2;13) Translocation in Alveolar Rhabdomyosarcomas Is A More Potent Transcriptional Activator than PAX3

Abstract: Tumor-specific translocations that result in altered expression of cellular genes occur frequently enough to be considered a general mechanism of oncogenesis (reviewed in references 18, 28, and 53). Chromosomal translocations may lead to oncogenesis via insertional activation in which one gene is placed under the control of an active expression element of another gene, typically an immunoglobulin or T-cell receptor locus, and thus inappropriately expressed. Translocation-mediated oncogenesis may also involve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
198
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(207 citation statements)
references
References 85 publications
6
198
0
Order By: Relevance
“…Moreover, in accordance with the AFX gene, the FKHR gene contains also a QIYEWM peptide motif upstream of the breakpoint. The PAX3/FKHR fusion protein is a more potent transcriptional activator than the normal PAX3 protein (Fredericks et al, 1995). Although the transcriptional potential of MLL might be augmented by the forkhead protein of AFX in a similar fashion, this possiblity is in contrast to current beliefs which suggest that the various MLL rearrangements diminish or destroy the function of the MLL protein.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, in accordance with the AFX gene, the FKHR gene contains also a QIYEWM peptide motif upstream of the breakpoint. The PAX3/FKHR fusion protein is a more potent transcriptional activator than the normal PAX3 protein (Fredericks et al, 1995). Although the transcriptional potential of MLL might be augmented by the forkhead protein of AFX in a similar fashion, this possiblity is in contrast to current beliefs which suggest that the various MLL rearrangements diminish or destroy the function of the MLL protein.…”
Section: Discussionmentioning
confidence: 87%
“…Antibodies used were: HA (Covance, Richmond, CA, USA); PAX3 (Fredericks et al, 1995); MyoD, myogenin, cyclin D1, cyclin D3, Rb, p21 (BD Pharmingen, San Jose, CA, USA); Myf5, cyclin A, cyclin E (Santa Cruz, Santa Cruz, CA, USA); b-actin (Sigma, St Louis, MO, USA); MHC (Developmental Studies Hybridoma Bank, Iowa City, IA, USA). Immunofluorescence was carried out on cells grown on collagen-coated glass coverslips.…”
Section: Emsa and Chromatin Immunoprecipitationmentioning
confidence: 99%
“…The consequence of these translocations is the expression of the PAX3-FKHR and PAX7-FKHR (collectively, PAX-FKHR) chimeric transcription factors containing the PAX DNA-binding domains and the potent FKHR transactivation domain. The functions of PAX-FKHR are modified compared to the wild-type PAX proteins due to changes in their abundance (Davis and Barr, 1997), transcriptional activity (Fredericks et al, 1995) and target gene recognition (Epstein et al, 1998). PAX-FKHR are therefore thought to contribute to the phenotype and malignancy of ARMS by aberrantly regulating PAX-specific target genes, signaling pathways and biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these structural rearrangements translocate the PAX3 gene at 2q35 to the FKHR gene at 13q14 (t(2;13)(q35;q14)); less frequently, a t(1;3)(q36;q14) translocation fuses PAX7 to FKHR. The PAX3-FKHR chimera is a more potent transcriptional activator than wild type pax3 (Fredericks et al, 1995), and presumably disrupts the normal regulation of target genes downstream of PAX3. Recently, it was reported that it is the PAX3 homeodomain recognition helix, and not the pairedbox DNA binding domain, that is required for transformation by the PAX3-FKHR chimera (Lam et al, 1999).…”
Section: Cytogenetic De®nition Of Rhabdomyosarcomamentioning
confidence: 99%